Superendividamento do consumidor: abordagem estrutural e comportamental à luz do princípio do crédito sustentável - Daura, Samir Alves (2018)
This work deals with the overindebtedness in the context of postmodern consumer society. In particular, a preventive model against the excessive indebtedness of the individual in Brazil was proposed, ideally to deal with the serious consequences caused by this phenomenon. The research assumed that overindebtedness is caused by structural and cultural factors, what re-quires a widely broad approach to cover all the complexity of such subject. Therefore, the study starts by defending the need to rethink consumer credit in Brazil based on the constitu-tional paradigm of sustainability, especially to guarantee the sustainable development of this service. In order to combat the existing structural factors of overindebtedness, this study de-fends the sustainable regulation of the credit market. Concerning cultural factors, the study analyzed the contributions offered by the Behavioral Economics theory and the Consumer Law looking to identify the main cognitive illusions that may undermine the decision-making process and consequently causing overindebtedness, aggravating consumer vulnerability, es-pecially when these illusions are manipulated by the credit industry. Finally, in order to cover excessive indebtedness in all its complexity, this work embrace the principle of sustainable credit as the foundation for a preventive model. Based on this model, it became necessary the implementation of the following measures together: compliance with the fundamental duty to inform; creation of a new guideline for civil liability of financial institutions; State responsible to regulate the credit market and create public policies aimed at debt prevention; financial ed-ucation. Methodologically, the work was formulated based on in-depth study of books and scientific articles by national and foreign authors and developed based on technical-bibliographic research, using both the inductive and argumentative method.